The Effect of Product Quality on Consumer Purchase Interest in Azarine Sunscreen Products at the Hijrah Store in Lhokseumawe City - Fahra, Zihan; Iryani, Lisa; Ameliany, Nanda; Maisyura, Maisyura; Sufi, Sufi (LPPM UIKA Bogor, 2024)
Product quality is the ability of a product to carry out its function, including reliability, durability, accuracy, ease of operation, and product repair, as well as other valuable attributes. Product quality is something that needs to receive primary attention from the company or producer, considering that the quality of a product is closely related to consumer satisfaction, which is the goal of the marketing activities carried out by the company. This research uses a quantitative approach which aims to find out whether product quality has a positive and significant influence on consumer purchase interest. The population in this study are all consumers who have purchased and used Azarine sunscreen at the Hijrah Store Lhokseumawe City, which is not known for certain and the sample was determined using the